Nonhuman primate abnormal behavior: Etiology, assessment, and treatment. Issue 6 (5th April 2022) - Lutz, Corrine K.; Coleman, Kristine; Hopper, Lydia M.; Novak, Melinda A.; Perlman, Jaine E.; Pomerantz, Ori
Abstract: Across captive settings, nonhuman primates may develop an array of abnormal behaviors including stereotypic and self‐injurious behavior. Abnormal behavior can indicate a state of poor welfare, since it is often associated with a suboptimal environment. However, this may not always be the case as some behaviors can develop independently of any psychological distress, be triggered in environments known to promote welfare, and be part of an animal's coping mechanism. Furthermore, not all animals develop abnormal behavior, which has led researchers to assess risk factors that differentiate individuals in the display of these behaviors. Intrinsic risk factors that have been identified include the animal's species and genetics, age, sex, temperament, and clinical condition, while environmental risk factors include variables such as the animal's rearing, housing condition, husbandry procedures, and research experiences. To identify specific triggers and at‐risk animals, the expression of abnormal behavior in captive nonhuman primates should be routinely addressed in a consistent manner by appropriately trained staff. Which behaviors to assess, what assessment methods to use, which primates to monitor, and the aims of data collection should all be identified before proceeding to an intervention and/or treatment. This article provides guidance for this process, by presenting an overview of known triggers and risk factors that should be considered, steps to design a comprehensive evaluation plan, and strategies that might be used for prevention or treatment. It also outlines the tools and processes for assessing and evaluating behavior in an appendix. This process will lead to a better understanding of abnormal behavior in captive primate colonies and ultimately to improved welfare. Abstract : Across settings, nonhuman primates may develop an array of abnormal behaviors. Intrinsic risk factors include the animal's species and genetics, age, sex, temperament, and clinical condition. Environmental risk factors include the animal's rearing, housing and husbandry, and research experiences. The expression of abnormal behavior in captive primates should be routinely assessed and treatment plans developed, if warranted. To provide practical advice, this paper outlines the tools and processes for assessing and evaluating behavior in an appendix. Highlights: Across settings, nonhuman primates may develop an array of abnormal behaviors including stereotypic and self‐injurious behavior. Intrinsic risk factors for abnormal behavior include the animal's species and genetics, age, sex, temperament, and clinical condition, while environmental risk factors include variables such as the animal's rearing, housing condition, husbandry procedures, and research experiences. The expression of abnormal behavior in captive nonhuman primates should be routinely assessed and treatment plans developed, if warranted.